Genomic gains and losses in malignant mesothelioma demonstrated by FISH analysis of paraffin-embedded tissues. Issue 1 (12th November 2011) - Takeda, Maiko; Kasai, Takahiko; Enomoto, Yasunori; Takano, Masato; Morita, Kouhei; Kadota, Eiji; IIzuka, Norishige; Maruyama, Hiroshi; Nonomura, Akitaka
Abstract : Aims: Malignant mesothelioma (MM) results from the accumulation of a number of acquired genetic events at the onset. In MM, the most frequent changes were losses in 9p21, 1p36, 14q32 and 22q12, and gains in 5p, 7p and 8q24 by comparative genomic hybridisation analysis. Although the diagnostic utility of 9p21 homozygous deletion by fluorescence in situ hybridisation (FISH) analysis in MM has been reported recently, alterations of other genes have not been examined to any great extent. This study analysed the frequency of various genomic gains and losses in MM using FISH analysis. Materials and methods: The authors performed a FISH analysis using paraffin-embedded tissues from 42 cases of MM. Results: Chromosomal losses in MM were found at 9p21 (83%), 1p36 (43%), 14q32 (43%) and 22q12 (38%), whereas gains were found at 5p15 (48%), 7p12 (38%) and 8q24 (45%). There were no cases of adenomatoid tumour, benign mesothelial multicystic tumour, reactive mesothelial hyperplasia or pleuritis showing any gains or losses. At least one genomic abnormality was identified in all cases of MM. Among various histological subtypes, the chromosomal abnormality tended to be more common in cases showing sarcomatous elements (biphasic or pure sarcomatoid) than in cases showing an epithelioid histology. Conclusions: The authors found various genomic gains and losses in MM by FISH analysis. The frequency of each genomic gain or loss examined in MM by FISH analysis almost agreed with the comparative genomic hybridisation technique in previous studies. This study suggests that genomic evaluation by FISH analysis might be helpful in distinguishing MM from benign mesothelial proliferation.